A new method to extract elastic modulus of brittle materials from Berkovich indentation. Issue 1 (January 2018) - Chen, Yan; Sullivan, MariAnne; Zhang, Anqi; Prorok, Barton C.
Abstract: This work describes a method to reliably measure the elastic modulus of brittle materials from Berkovich indents under the continuous stiffness mode. It involves depositing a metallic film at the surface of the tested material to absorb the inelastic damage caused by the penetrating indenter. The Zhou-Prorok model was employed and rearranged to decouple the film and substrate contributions. This converted it into a hyperbolic form that approached an asymptote as the indenter approaches the film/substrate interface. This asymptote was described by a simple linear approximation whose slope directly revealed the substrate's elastic modulus. The method enabled the elastic behavior of the brittle ceramic to be assessed without the indenter penetrating it. In fact, this method can assess properties of an unknown film/substrate composite as long as one has an estimate of the film thickness and the film can appreciably plastically deform.